THEOLOGICAL FORMATION OF CONSECRATED WOMEN: A NECESSARY TOOL FOR NEW EVANGELIZATION - Noelina, Nakato (Asian Horizons, 2018)
New evangelization demands that consecrated women have a thorough awareness of the theological significance of challenges of our time. These challenges must be weighed with careful joint discernment with the view to renew the mission (Vita Consecrata, no. 81). The rationale behind this statement is that, the problems and difficulties by which people of today are burdened and anguished, prompt them to ask challenging theological questions, which sometimes overwhelm the ministers of the word. Very often, we come across many questions, seeking clarification of our faith. This clearly shows that the people who are evangelized today are rapidly moving beyond the stage of simple believing to a more intelligible faith that can give answer to their problems. Hence, this work is to advocate the right and duty of religious women to education in Sacred Sciences (c. 660) so that they may remain relevant in their prophetic mission. The work is divided into four sections: the first section gives the meaning of the ministry of the word, its goals, sources agents and means. The second section shows the involvement of religious women in the ministry of the word using various means. The third section explicates the challenges faced by these minsters in their ministry. The fourth and last section gives some recommendations for the renewal of the mission of religious women.